ANALISIS PEMBIAYAAN PENCEGAHAN STUNTING DI KABUPATEN BADUNGDENGAN PENDEKATAN DISTRICT HEALTH ACCOUNT - Made Agus Sugianto; I Gusti Ayu Ngurah Lita Rumiati, (Jurnal Kesehatan Medika Udayana, 2020)
Background: Stunting rates in Badung Regency show an upward trend while information on funding and utilization and who is the beneficiary is still very limited. Therefore, through the District Health Account, it is expected that decision makers will be able to overcome the problem of adequacy, equity, efficiency, effectiveness and sustainability. Objective: to analyze the cost of stunting prevention using the District Health Account Approach. Method: This research is descriptive using cross-sectional studies, data collection through in-depth interviews to the manager of the District Health Office in Bandung District and the manager of the Provincial Health Department of Bali Nutrition and documentation studies. Results: Most stunting prevention costs came from the central government (70.16%), and the highest proportion of the budget was managed by puskesmas (56.74%). Most of the stunting prevention funding was used for operational expenditure (79.43%), and the financing was mainly directed towards all age groups (48.53%). In the lowest 40% (poor families) the average monthly expenditure is only Rp.438,944 or equivalent to 1,962.55 Kcal per person per day, this figure is below the stipulated calorie adequacy rate of 2,200 - 2,500 Kcal per person per day. Conclusion: The cost of stunting prevention program is only sourced from the government, where most costs come from the central government (70.16%), far exceeding the Badung Regency Government (21.16%) and the Provincial Government of Bali (8.69%). The cost of puskesmas stunting prevention program is used for operational expenses for the bottom 40% (poor families) whose average monthly expenditure is only equivalent to consuming 1,962.55 Kcal of food per person per day. Badung Regency Government to increase the financing of stunting prevention which is prioritized for the lowest 40% population (poor population).Keywords: Stunting; Financing; Badung Regency